Product Quality, Cost Position, and Business Performance: A Test of Some Key Hypotheses - Phillips, Lynn W. (Institutional Knowledge at Singapore Management University, 1983)
This study uses a causal modelling methodology to examine competing methodological and theo- retical hypotheses concerning the effects of prod- uct quality on direct costs and business unit re- turn on investment (ROI). Results show that the PIMS' measures under study exhibit high reliabil- ity across all samples. The findings fail to support the widely held view that a high relative quality position is incompatible with achieving a low rel- ative cost position in an industry.